Overcoming challenges in human saliva gene expression measurements - Ostheim, Patrick; Tichý, Ales; Sirak, Igor; Davidkova, Marie; Stastna, Marketa Markova; Kultova, Gabriela; Paunesku, Tatjana; Woloschak, Gayle; Majewski, Matthaeus; Port, Matthias; Abend, Michael (Scientific reports, 2020)
Saliva, as a non-invasive and easily accessible biofluid, has been shown to contain RNA biomarkers for prediction and diagnosis of several diseases. However, systematic analysis done by our group identified two problematic issues not coherently described before: (1) most of the isolated RNA originates from the oral microbiome and (2) the amount of isolated human RNA is comparatively low. The degree of bacterial contamination showed ratios up to 1:900,000, so that only about one out of 900,000 RNA copies was of human origin, but the RNA quality (average RIN 6.7 + /- 0.8) allowed for qRT-PCR. Using 12 saliva samples from healthy donors, we modified the methodology to (1) select only human RNA during cDNA synthesis by aiming at the poly(A)+-tail and (2) introduced a pre-amplification of human RNA before qRT-PCR. Further, the manufacturer's criteria for successful pre-amplification (Ct values ≤ 35 for unamplified cDNA) had to be replaced by (3) proofing linear pre-amplification for each gene, thus, increasing the number of evaluable samples up to 70.6%. When considering theses three modifications unbiased gene expression analysis on human salivary RNA can be performed.
Keywords: exprese genu; bakteriální RNA; transkriptom; Gene Expression; Male; kvantitativní polymerázová řetězová reakce; Saliva; RNA, Ribosomal, 18S; komplementární DNA; Transcriptome; Adult; dospělí; mužské pohlaví; stanovení celkové genové exprese; Real-Time Polymerase Chain Reaction; Gene Expression Profiling; lidé; RNA; ženské pohlaví; Humans; sliny; RNA ribozomální 18S; DNA, Complementary; Female; RNA, Bacterial